2017
DOI: 10.1104/pp.17.00805
|View full text |Cite
|
Sign up to set email alerts
|

Cytokinin-Auxin Crosstalk in the Gynoecial Primordium Ensures Correct Domain Patterning

Abstract: The Arabidopsis (Arabidopsis thaliana) gynoecium consists of two congenitally fused carpels made up of two lateral valve domains and two medial domains, which retain meristematic properties and later fuse to produce the female reproductive structures vital for fertilization. Polar auxin transport (PAT) is important for setting up distinct apical auxin signaling domains in the early floral meristem remnants allowing for lateral domain identity and outgrowth. Crosstalk between auxin and cytokinin plays an import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 75 publications
1
33
0
Order By: Relevance
“…A key step in ovule development is determination of the position and number of ovule primordia in the CMM (Cucinotta et al , ). CMM and ovule primordia formation are both controlled by regulatory genes, as well as by several plant growth regulators, including auxin, cytokinin (CKs), and brassinosteroids (BRs) (Bartrina et al , ; Bencivenga et al , ; Huang et al , ; Galbiati et al , ; Reyes‐Olalde et al , ; Cucinotta et al , , ; Müller et al , ). Recently, we have demonstrated that gibberellins (GAs) also play an important role in modulation of ovule number in Arabidopsis as well as in tomato and rapeseed (Gomez et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…A key step in ovule development is determination of the position and number of ovule primordia in the CMM (Cucinotta et al , ). CMM and ovule primordia formation are both controlled by regulatory genes, as well as by several plant growth regulators, including auxin, cytokinin (CKs), and brassinosteroids (BRs) (Bartrina et al , ; Bencivenga et al , ; Huang et al , ; Galbiati et al , ; Reyes‐Olalde et al , ; Cucinotta et al , , ; Müller et al , ). Recently, we have demonstrated that gibberellins (GAs) also play an important role in modulation of ovule number in Arabidopsis as well as in tomato and rapeseed (Gomez et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…Auxin and cytokinin were shown to interact both antagonistically and synergistically during the development of root and shoot apical meristems and these interactions involve coordination of signaling, biosynthesis, and transport pathways to delineate stem cell niches, meristem growth, vascular pattern formation, and organ initiation in the shoot (Besnard et al., ; Bishopp et al., ; Chickarmane, Gordon, Tarr, Heisler, & Meyerowitz, ; Dello Ioio et al., ; Truskina & Vernoux, ). Auxin–cytokinin interactions have also been shown to be essential for the control of the development of determinate meristems such as those needed for gynoecium development (Muller, Larsson, Spichal, & Sundberg, ; Reyes‐Olalde et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Which both of auxin and cytokinin are usually required for growth or morphogenesis. Auxin blocks cytokinin signaling (Müller et al, 2017) while cytokinins can inhibit at least some of the action of auxin. Cotyledonary node with section of cotyledon was subcultured or re-cultured in MS medium containing PGR according to treatments.…”
Section: Effect Of Plant Growth Regulator Types Concentrations and Tmentioning
confidence: 99%